Internet Support Communities, Online Peer Support, Social Networks/Social Media & Internet Use by Hospitalized Patients - Laghos, Andrew; Nicolaides, Christian (My University, 2016)
The purpose of this research was to explore internet support communities, online peer support, social networks/social media and internet use by hospitalized patients. Communication, relationships, education, language, and in general human connections through the internet are all important factors of how the World Wide Web is used. We investigated Internet support communities for people with health problems. More specifically, the objective of this study was to find out how people who have been hospitalized and are awaiting major surgery use the Internet to get educated about their situation and recovery. Results show that through the use of the Internet and online peer support, the participants received psychological support, hope, and guidance to recovery, while conclusions attribute this to feelings of reduced loneliness and increased understanding by people who have been through similar situations. Finally, the participants rated the internet and the online peer support that they received as extremely important.
Keywords: Online peer support; Social networks; Social media; Internet use; Internet support communities; Hospitals; Patients